Blockchain- Rapid diagnostic tests for vector borne disease control - ramli, nabilah (2019)
Vector-borne diseases have moved into new territory due to unplanned urbanization, increased movement of people and goods, environmental changes and biological challenges, such as vectors resistant to insecticides and evolving strains of pathogens. Systematic, ongoing collection, collation, and analysis of data and the timely dissemination of information to those who need to know so that the action can be taken. Advances that support evidence-based vector control such as information communication technologies that support real-time data capture or social media, or risk stratification and predictive geo-informatics tools such as geographical information systems, remote sensing, and climatic models can be leveraged to further optimize planning and implementation.